Pengaruh Pandemi COVID-19 Terhadap Meningkatnya Pernikahan Pada Remaja Di Kelurahan Cibojong Desa Kadubeureum Kecamatan Padarincang Kabupaten Serang Tahun 2022 - Khayati Nupus; Nofa Anggraini (Jurnal Keperawatan Muhammadiyah, 2022)
Background: The factors behind the occurrence of child marriages are among others due to poverty, children's willingness, education, family and also cultural factors. Research Objectives: To determine the effect of the Covid 19 pandemic on the increase in marriage among teenagers in Cibojong Village, Kadubeureum Village, Padarincang District, Serang Regency in 2022. Research Method : This type of research is analytic observational in a retrospective case control with a quantitative approach . The sample size is 80 people in young women. The sampling technique used is non-probability sampling with purposive sampling method. Research results: there is an effect of being exposed to covid 19, knowledge, parental education, parental occupation, dropping out of school and history of marriage age on marriage in adolescents with an Asimp.sign value < 0.05. The results of the OR calculation show that being exposed to covid 19 12 times experienced teenage marriage compared to being exposed to negative covid 19 (95% CI 3,801–37,884). The results of the OR calculation show that 23,692 school dropout respondents experienced teenage marriages compared to those who did not drop out (95% CI 6,098 – 92,054). The results of the OR calculation show that the respondent's parental marriage history is less than 19 years, 4,091 times experienced adolescent marriage compared to the history of parental marriage age of more than 19 years (95% CI 2,448 – 6,838) Conclusions and Suggestions: For health services for promotion of adolescents, especially regarding the factors that cause early marriage, so that it can change adolescents' perceptions of early marriage. and the government can overcome it during the COVID-19 pandemic so that they get solutions related to economic problems in the community, especially those with previously low economic status.